PENERAPAN PENDEKATAN STRUKTURAL METODE THINK PAIR SHARE(TPS)PADA MATERI LINGKARANUNTUK MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA SISWA - Azizah, Dewi (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The purposes of the research were to increase the studentsâ activities of learning mathematic and to improve studentsâ learning achievements by using TPS method. The research was a collaborative achievement research between the mathematic teacher, headmaster and the writer. The eighth grade students of SMP N 2 Wiradesa were the subject of the research. This research was a class action research. The results showed that TPS method could improve the studentsâ activities and achievements significantly. The studentsâ activities rose 34,15% to 75,61%Â  and studentsâ achievements rose from 36,59 % to 80,49%. Kata Kunci: activity, TPS, achievement